Massive Localized Lymphedema Revisited. Issue 1 (January 2015) - Chopra, Karan; Tadisina, Kashyap K.; Brewer, Michael; Holton, Luther H.; Banda, Abhishake K.; Singh, Devinder P.
<x xml:space="preserve">Abstract</x> Abstract Massive localized lymphedema (MLL) is a rising and potentially fatal complication of the obesity epidemic. Described as a benign lymphoproliferative overgrowth of obese patients, MLL is a form of secondary lymphedema, caused by the obstruction of lymphatic flow, with characteristic clinical and histological presentation. Patients have a large mass with classic skin changes often accompanied by lymphatic weeping that require complex reconstruction. Although oftentimes benign, if left untreated, MLL can progress to angiosarcoma, further supporting the need for more research into MLL and its sequelae. We present a unique case of MLL of the mons pubis in a 52-year-old man with a body mass index of 75.7 kg/m2. The literature was comprehensively reviewed with a total of 65 cases of MLL being described, 9 of which resulted in angiosarcoma (10.3% of all cases), 6 of which resulted in death (9.2% of all cases). We found a female predominance of 1.24 to 1, an average weight of 183 kg, and a 48.5% majority of cases in the thigh.